PENGARUH WILLIAM’S FLEXION EXERCISE DENGAN LANTUNAN AYAT SUCI AL QUR’AN TERHADAP SKALA NYERI HAID (DISMENOREA) PADA REMAJA PUTRI PANTI ASUHAN DARUL ULUM YOGYAKARTA: THE EFFECT OF WILLIAM 'S FLEXION EXERCISE WITH THE QUR'ANIC VERSES ON THE SCALE OF MENSTRUAL PAIN (DISMENOREA) IN ADOLESCENT AT THE DARUL ULUM ORPHANAGE YOGYAKARTA - Astuti, Dwi; Adkhana, Dian Nur (Stikes Wira Medika Bali, 2019)
Background: menstrual pain (dysmenorrhea) is pain that occurs before or during menstruation. Dysmenorrhea can interfere with adolescent activities and can indirectly interfere with their quality of life if left untreated. Objective: to determine the effect of William's flexion exercise and the Qur'anic verses on the scale of menstrual pain (dysmenorrhea) in adolescent at the Darul Ulum Orphanage in Yogyakarta. Method: This type of research uses a Pre-Experimental research design with one group pre-post test design. The sampling technique used purposive sampling with a sample of 20 young women at the Darul Ulum Orphanage in Yogyakarta. The data analysis technique used a paired t-test, collecting data with an observation sheet consisting of the Numeric Rating Scale. Results: The results showed that the average intensity of dysmenorrhea before intervention was 6.15 while after intervention 4.60. The paired t-test results obtained p value 0,000 <0,05. Conclusion: There was an influence of William's flexion exercise and the Qur'anic verses on the scale of menstrual pain (dysmenorrhea) at the Darul Ulum Orphanage in Yogyakarta.